Legal Certainty of Stopping the Prosecution of Criminal Cases By The Prosecutor's Office in a Restorative Justice Approach - Hamrin Hamrin; Kumba Digdowiseiso (Budapest International Research and Critics University, 2022)
Restroative justice is in principle limited only to actors who have just committed crimes and are not recidivists, and only to certain types of minor crimes. The purpose of the research in this preparation is to analyze the termination of the prosecution of criminal problems by the prosecutor's office through a restorative justice approach and a form of legal certainty for the termination of criminal problems by the prosecutor's office through the Restorative Justice approach. This research uses a normative juridical approach. The type of legal material used is primary, secondary and tertiary legal material analysis used is using qualitative alalysis. Based on the results of research, it is proven that the prosecution of criminal problems can be tried with a restorative justice approach to criminal acts that are tried only to be threatened with a fine or threatened with imprisonment for no more than 5 years, criminal acts are tried with the value of fact objects or the value of losses caused by criminal acts of not more than IDR 2.5 million. The form of legal certainty with the existence of restroative justice is the involvement of victims and actors directly in solving criminal problems. The restorative justice approach in this regard prioritizes efforts to link the participation of victims and actors to share legal certainty for victims.